Exploring content and psychometric validity of newly developed assessment tools for itch and skin pain in atopic dermatitis - Louise Newton; Amy M. DeLozier; Philip C. Griffiths; Jennifer N. Hill; Stacie Hudgens; Tara Symonds; Jonathon C. Gable; Jim Paik; Kathleen W. Wyrwich; Lawrence F. Eichenfield; Linda Abetz-Webb; Jonathan I. Silverberg (Journal of Patient-Reported Outcomes, 2019)
Abstract Background Atopic dermatitis (AD) is a common skin disorder characterized by chronic inflammation, altered skin barrier function, and inflammatory cell skin infiltration that decreases health-related quality of life (HRQoL). The study objective was to understand the patient perspective of AD burden and determine suitable patient-reported outcome (PRO) measures. Methods This mixed methods study involved the collection of qualitative and quantitative information from adults (≥ 18 years old) and adolescents (12 – 17 years old) with clinician-confirmed AD regarding their experiences of AD symptoms and its impact on HRQoL. The first part of the study included three stages: in-person concept elicitation (CE) interviews, a 2-week daily electronic diary (eDiary) study, and in-person cognitive debriefing (CD) interviews. An Itch numeric rating scale (NRS) (v1.0) and a Skin Pain NRS (v1.0) evaluation during CD interviews required participants to think about their ‘worst’ itch and ‘worst’ skin pain in the past 24 h. Other PRO measures allowed for psychometric testing. The second part of the study involved telephone-depth interviews (TDIs) and qualitative feedback from participants who had not participated in the CD interviews. Qualitative data were thematically analyzed. Psychometric evaluation of NRS measures was performed using eDiary data. Results In the CE interviews, itch and/or itching and skin pain were the most prevalent symptoms consistently discussed by participants. Both NRS measures demonstrated strong psychometric reliability and were applicable across ages with suitable concurrent validity. During the CD interviews, some participants focused their answers on their ‘average’ itch/itching in the past 24 h, rather than their ‘worst’ itch. Some participants answered the Skin Pain NRS thinking about general pain or other types of pain, rather than skin pain specifically. Consequently, modifications to both measures addressed these issues and re-tested as paper-and-pen versions in subsequent TDIs. Itch NRS (v2.0) modifications helped participants focus on their worst itching. Most participants preferred Skin Pain NRS v2.0b, which included skin pain descriptors. Conclusions Itching and skin pain are the most important and relevant AD symptoms. The Itch NRS (v2.0) and Skin Pain NRS (v2.0b) appear to be appropriate endpoints for the assessment of itching and skin pain severity for clinical trials with adults and adolescents with AD.